Evidence for brain glucose dysregulation in Alzheimer's disease. Issue 3 (19th October 2017) - An, Yang; Varma, Vijay R.; Varma, Sudhir; Casanova, Ramon; Dammer, Eric; Pletnikova, Olga; Chia, Chee W.; Egan, Josephine M.; Ferrucci, Luigi; Troncoso, Juan; Levey, Allan I.; Lah, James; et al.
Abstract: Introduction: It is unclear whether abnormalities in brain glucose homeostasis are associated with Alzheimer's disease (AD) pathogenesis. Methods: Within the autopsy cohort of the Baltimore Longitudinal Study of Aging, we measured brain glucose concentration and assessed the ratios of the glycolytic amino acids, serine, glycine, and alanine to glucose. We also quantified protein levels of the neuronal (GLUT3) and astrocytic (GLUT1) glucose transporters. Finally, we assessed the relationships between plasma glucose measured before death and brain tissue glucose. Results: Higher brain tissue glucose concentration, reduced glycolytic flux, and lower GLUT3 are related to severity of AD pathology and the expression of AD symptoms. Longitudinal increases in fasting plasma glucose levels are associated with higher brain tissue glucose concentrations. Discussion: Impaired glucose metabolism due to reduced glycolytic flux may be intrinsic to AD pathogenesis. Abnormalities in brain glucose homeostasis may begin several years before the onset of clinical symptoms. Highlights: Brain tissue glucose is associated with severity of Alzheimer's disease (AD) pathology and symptom onset. Reduced brain glycolytic flux is associated with severity of AD pathology and symptom onset. Neuronal glucose transporter‐3 is lower in AD. Lower glucose transporter‐3 levels are associated with more severe AD pathology. Increase in plasma glucose decades before death is related to higher brain glucose.